Experimental Investigations on the Strength and Serviceability of Biaxial Hollow Concrete Slabs (Journal of Engineering, 2016)
Biaxial hollow slab is a reinforced concrete slab system with a grid of internal spherical voids included to reduce the self-weight. This paper presents an experimental study of behavior of one-way prestressed concrete bubbled slabs. Twelve full-scale one-way concrete slabs of (3000mm) length with rectangular cross-sectional area of (460mm) width and (150mm) depth. Different parameters like type of specimen (solid or bubbled slabs), type of reinforcement (normal or prestress), range of PPR and diameter of plastic spheres (100 or 120mm) are considered. Due to the using of prestressing force in bubbled slabs (with ratio of plastic sphere diameter D to slab thickness H, D/H=0.67), the specimens showed an increase in ultimate load capacity ranging between (79.3% and 125%) and a decrease in the deflection at service load of about (9.8% to 12%) with respect to the control bubbled reinforced concrete slab. Also, it is found that, the bubbled slabs have about (79% to 86%) of the ultimate load capacity of a similar reference solid slab. At the same time the influence of voids present in the bubbled slabs is reflected in a decrease in the first cracking load by about (14.8% to 29.6%) in comparison with solid slabs.